Índice de sustentabilidade do perímetro irrigado Baixo Acaraú-Ceará - Lopes, Fernando Bezerra (2008)
The aimed of this work was an integrated sustainability analysis of the Irrigated Perimeter of Baixo Acaraú (PIBAU) sited in Acaraú basin, Ceará, Brazil. The analysis was labeled by an agro ecological sustainability index (ASI). The approach was based on 22 cross-over form applied to small producers that live in the PIBAU. In the irrigated areas selected to perform the interviews, it was developed the irrigation system evaluation. Factory Analysis/Principal Components Analysis (FA/PCA) was employed to select the factors sustainability indicators of the irrigated perimeter as well as to define the agro ecological sustainability index. Results showed that 64% of the producers had a power education and 77% of them had no experience with irrigation agriculture before. Also, it was identified that only 18% of irrigation systems presented an excellent CUD, while 28% of them were classified with a bad performance. According to the sensitive test effectuated by FA/PCA, only 12 of 27 variables that composed the initial matrix were significant to explain the total variance of data set. The 12 variables selected by the model were grouped in five factors explaining 79.14% of the total variance. The factors loading indicated that the PIBAU sustainability is, principally, related to the lack of acknowledgment as well as the used of suitable management of agricultural practices. The sustainability index of each productive units ranges from 0.283 to 0.916 and the average was 0.538. Only 9.0% of the pooled productivity were classified as sustainable, while 18.2% of them presented a kind of sustainability. Almost the half of producers (45.5%) showed a threatened sustainability and the others (27.3%) were in unsustainable condition. Also, it was identified that some units with a good irrigation system performance, without of salinization risk presented a low sustainability index (0.371). This is explained by the fact the index express an integration of different variables. Even though, no risk of salinization was identified, this work registered an addition high of significance of salt in the irrigated area when compared to undisturbed one.